An Underwater Sound Propagation Model based on Ray Tracing for Virtual Reality - Castro, Guilherme Silva de; Malheiros, Marcelo de Gomensoro; Bicho, Alessandro de Lima (Anais do Simpósio de Realidade Virtual e Aumentada (SVR), 2024)
The emergence of new technologies for Virtual Reality has provided the user with a greater feeling of immersion. This immersion includes visual and sound perception, making realistic models for the light and sound behavior necessary. The Computer Graphics field is already well consolidated, but studies still need to be conducted on sound behavior in Virtual Reality. In this context, this work describes a new simplified underwater sound propagation model using the Unity game engine. The proposed approach allows the development of virtual environments with realistic underwater sound effects. Based on the ray-tracing algorithm, the implementation presents satisfactory results considering static sound sources. This paper describes the proposed model and a few test scenarios, and discusses the results obtained.